Double sided assembly line balancing problem by using ranked positional weight method: An automative industrial case study - Shuliana Ghazali (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Line balancing is about arranging a production line so that there is an even flow of production from one work station to the next. There is an urge to achieve high productivity, improve the level of efficiency and reducing expenditure cost in a manufacturing process. The aim of this study to minimize the number work station for assembly line balancing. It is also to solve the assembly line balancing problem by using Ranked Positional Weight Heuristic Method.